Delivering an off-grid transition to sustainable energy in Ethiopia and Mozambique - Gebreslassie, MG; Cuvilas, C; Zalengera, C; To, LS; Baptista, I; Robin, E; Bekele, G; Howe, L; Shenga, C; Macucule, DA; Kirshner, J; Mulugetta, Y; et al. (BioMed Central, 2022)
Background: Off-grid and decentralized energy systems have emerged as an alternative to facilitate energy access and resilience in a flexible, adaptable way, particularly for communities that do not have reliable access to centralized energy networks both in rural and urban areas. Much research to date on community energy systems has focused on their deployment in Europe and North America. This paper advances these debates by looking at how community energy systems can support energy transitions in Africa. Specifically, it asks: what role can community energy systems play in the energy transition in East and Southern Africa? Results: This article investigates the potential for community energy to foster sustainable and just energy transitions in two countries in East and Southern Africa, namely Ethiopia and Mozambique. To do so, it explores transformations in Ethiopia and Mozambique’s energy systems through the lens of energy landscapes. This concept enables us to situate energy transitions within recent developments in energy governance and to understand current and future possibilities for change through the involvement of communities that currently lack access to reliable and clean energy. Our results show that when countries face the prospects of lucrative energy investments in natural gas or large hydropower, renewables are often deprioritized. Their suitability to address energy challenges and access gaps is de-emphasized, even though there is little evidence that investment in large-scale generation can handle the energy needs of the most disadvantaged groups. Initiatives and policies supporting community-focused renewable energy have remained limited in both countries. They tend to be designed from the top-down and focused on rural areas when they exist. Conclusions: Energy transitions in Ethiopia and Mozambique, and many other countries with significant gaps in access to centralized energy systems, require putting inclusivity at the forefront to ensure that energy policies and infrastructure support the well-being of society as a whole. As long as investments in off-grid energy continue to depend on international organizations’ goodwill or development aid programs outside the ambit of national energy plans, energy access gaps will remain unaddressed, and there will not be a genuine and just transition to sustainable energy.